Metacognitive Strategies Applied by University Students of Unimed in Listening Comprehension - Cici Handayani; Lince Sihombing; Sri Minda Murni (Universitas Negeri Medan, 2015)
This research was aimed at finding out the degree of metacognitive strategies applied by English Department students of UNIMED in listening comprehension and the difficulties of application metacognitive strategies by English Department students of UNIMED in listening comprehension. The study was conducted to 28 students in fourth semester of English Department of UNIMED Medan. Since the study was a qualitative research, the data were analyzed qualitatively by means of observation, questionnaire, Think Aloud Protocols (TAP) and interview. The questions in questionnaire and interview were based on Chammot’s and O’Malley’s. As findings, the data analysis shows the degree of application metacognitive strategies. The students’ application is low since they only applied some parts of sub-categories in metacognitive strategies as their habit in doing their listening task. They often lose their concentration while they are listening to the speakers. They cannot write down the sentences that were uttered by the speakers and write down the unuttered ones. They cannot comprehend the listening well and it makes them feel worry, doubt, nervous and others negative feeling. Based on the results, some implications and suggestions for future research are discussed. Keywords: Listening comprehension; Listening strategies; Metacognition; Metacognitive Strategies